"Eu mato": The Linguistic and Religious Rewriting of the Tupí under Portuguese Missionary Rule (1555-1630) - Cravens, Marlena Petra (Tusaaji: A Translation Review, 2020)
Abstract: This paper investigates the relationship between Portuguese missionary grammars, imperial-indigenous relations, and Tupí resistance between 1555 and 1630. Focusing on José de Anchieta’s popular grammar Arte de gramática de língua mais usada na costa do brasil (1555) and Luís Figueira’s Arte da Língua Brasílica (1621), it argues that the shifting focuses of these texts represent the values of the Jesuit order and the interests of Portugal in the New World. Portuguese missionaries moved from an earlier emphasis on trade and Christian conversion with an exclusively oral culture toward a more aggressive and insidious campaign for cultural and linguistic erasure in the region. While previous scholarship has examined changes in Tupí phonemes, morphemes, and syntax between the grammars, this study instead investigates the historical changes pertinent between these texts, their constructed relationships between Portuguese and Tupí, and shifts in their lexical emphases. Keywords: colonial translation; grammars; Jesuit missionaries; cultural erasure; Tupí-Guaraní